2007
DOI: 10.1093/hmg/ddm207
|View full text |Cite
|
Sign up to set email alerts
|

Association of distinct allelic haplotypes of DISC1 with psychotic and bipolar spectrum disorders and with underlying cognitive impairments

Abstract: Bipolar disorder (BPD) and schizophrenia (SCZ) have at least a partially convergent aetiology and thus may share genetic susceptibility loci. Multiple lines of evidence emphasize the role of disrupted-in-schizophrenia-1 (DISC1) gene in psychotic disorders such as SCZ. We monitored the association of allelic variants of translin-associated factor X (TSNAX)/DISC1 gene cluster using 13 single-nucleotide polymorphisms (SNPs) in 723 members of 179 Finnish BPD families. Consistent with an earlier finding in Finnish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 58 publications
2
81
0
Order By: Relevance
“…45 This result has been replicated independently for bipolar spectrum disorders and further strengthened by the finding of an association between HEP3 and rate of perseverative errors in the California Verbal Learning Test, a cognitive endophenotype for schizophrenia. 46 An extended region including HEP3 and two additional SNPs (rs1615409 and rs766288) was found to be over-represented in a sample of Finnish twins suffering from schizophrenia and also associated with impaired spatial working memory, increased reaction time to visual targets and reduced prefrontal grey matter. 27 Another study, in a North American sample, found an association between schizo-affective disorder and an under-transmitted haplotype carrying the A allele of rs3738401.…”
Section: Association Of Disc1 Missense Variants With Ursmentioning
confidence: 98%
See 1 more Smart Citation
“…45 This result has been replicated independently for bipolar spectrum disorders and further strengthened by the finding of an association between HEP3 and rate of perseverative errors in the California Verbal Learning Test, a cognitive endophenotype for schizophrenia. 46 An extended region including HEP3 and two additional SNPs (rs1615409 and rs766288) was found to be over-represented in a sample of Finnish twins suffering from schizophrenia and also associated with impaired spatial working memory, increased reaction time to visual targets and reduced prefrontal grey matter. 27 Another study, in a North American sample, found an association between schizo-affective disorder and an under-transmitted haplotype carrying the A allele of rs3738401.…”
Section: Association Of Disc1 Missense Variants With Ursmentioning
confidence: 98%
“…As mentioned above, rs3738401 is included in the haplotype HEP3, previously associated with cognitive dimensions in schizophrenia. 27,28,46 Despite the statistical association, it is difficult to eliminate the possibility that the global severity of the disease or other pathological dimensions, such as cognitive dysfunction, is in fact the mediating factor in this relationship. Complementary studies comparing response to antipsychotic medication with the severity of the disease or cognitive impairments along with genetic molecular investigations may help untangle this issue.…”
Section: Association Of Disc1 Missense Variants With Ursmentioning
confidence: 99%
“…The involvement of DISC1 in the etiology of BD was first suggested by Palo et al 40 . These authors suggested that polymorphisms in DISC1 contribute to variations in the psychotic features of bipolar spectrum disorder.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, several candidate genes have been associated with both schizophrenia and bipolar diagnoses (e.g. Hodgkinson et al, 2004, Funke et al, 2005, Green et al, 2005, Palo et al, 2007, leading some authors to suggest that psychosis may be a better phenotype for genetic studies than DSM diagnosis Owen, 2005, Owen et al, 2007).…”
Section: Genetics and The Definition Of Bipolar Disordermentioning
confidence: 99%
“…Similarly, several candidate genes have been associated with both schizophrenia and bipolar diagnoses (e.g. Hodgkinson et al, 2004, Funke et al, 2005, Green et al, 2005, Palo et al, 2007, leading some authors to suggest that psychosis may be a better phenotype for genetic studies than DSM diagnosis Owen, 2005, Owen et al, 2007).Kendler (2006) warns against adopting a gene-centric view of psychiatric nosology, arguing that the effect sizes of individual genes are currently too modest to justify overthrowing other ways of defining the boundaries between disorders. Nevertheless, identifying genetic variants that have pleiotropic effects across disorders may reveal fundamental biologic mechanisms that could provide targets for novel and more broad-spectrum interventions.…”
mentioning
confidence: 99%